Judicialização da educação infantil: desafios e dimensões evidenciados na produção acadêmica brasileira (2009-2019) - Araújo, Maciela Mikaelly Carneiro de (2022)
This research sought to answer the question of the challenges highlighted in the academic production on the judicialization of Early Childhood Education, regarding the right of access to day care centers and preschools. For this, it aimed to analyze the judicialization of early childhood education in the existing academic production in the Graduate Programs in Education in Brazil, on the guarantee of the right to day care centers and preschools, between 2009 and 2019. historicity of the right to Early Childhood Education and its relationship with the State and public policies, as well as the effects of judicialization on the education system. In this way, it is characterized as a qualitative research, of the state of the art or state of knowledge type. The results of the academic study showed that judicialization is a palliative and punctual action to resolve the issue of lack of access, as it is not enough to guarantee the right of some children through legal actions, without planning for the long term and without having a budget to meet the right of all children who need places in early childhood schools. This impacts on the construction of the conception of rights and early childhood education built in the history of Brazilian educational policies, in order to overcome the welfare vision and philanthropic service. It is also pertinent to consider that the fulfillment of the right to early childhood education for children still faces challenges such as the prioritization of resources for Elementary Education and the lack of quality, engendered by the effects of judicialization on pedagogical issues, such as overcrowding of classrooms, and lack of human and material resources to meet the demand of children who arrive at schools through judicial enrollment. In this sense, this research opens space for new studies on the subject in the Graduate Programs in Education, especially in the Northeast region, which has a lack of research on the judicialization of Early Childhood Education.